ANALISIS EFISIENSI PENGGUNAAN BELANJA DAN JUMLAH PEGAWAI TERHADAP INDEKS KEPUASAN MASYARAKAT: STUDI PADA SATUAN KERJA PERANGKAT DAERAH KOTA MALANG TAHUN 2013 - Antya Sukmawati; Didied Poernawan Affandy (Jurnal Ilmiah Mahasiswa FEB, 2013)
This research was held to see the efficiency level of Government Working Units in Malang Municipality by using Data Envelopment Analysis (DEA) as the research method. Variable Return to Scale (VRS) assumption and both input-oriented and output oriented are used. The result gives the same benchmarks, those are Environmental Units, Development Division, and Food Security Office. Input-oriented method shows that three units belong to group I (very efficient), five units belong to group II (efficient), six units belong to group III (reasonably efficient), four units belong to group IV (inefficient), and 22 units or more than 50% of sample belong to group V (very inefficient). Meanwhile with output-oriented method shows that three units belong to group I and the rest or 37 units belong to group II. Each units cannot be generalized to minimizing input variable because the differences in job description, while the output variable can be maximized by training to increase the quality employees’ performance and service.Keywords: efficiency, DEA, Data Envelopment Analysis, employee, Citizen Satisfaction Index